Systematic re‐evaluation of SCN5A variants associated with Brugada syndrome. (31st October 2018) - Denham, Nathan C.; Pearman, Charles M.; Ding, Wern Yew; Waktare, Johan; Gupta, Dhiraj; Snowdon, Richard; Hall, Mark; Cooper, Robert; Modi, Simon; Todd, Derick; Mahida, Saagar
Abstract: Background: A large number of SCN5A variants have been reported to underlie Brugada syndrome (BrS). However, the evidence supporting individual variants is highly heterogeneous. Objective: We systematically re‐evaluated all SCN5A variants reported in BrS using the 2015 American college of medical genetics and genomics and the association for molecular pathology (ACMG‐AMP) guidelines. Methods: A PubMed/Embase search was performed to identify all reported SCN5A variants in BrS. Standardized bioinformatic re‐analysis (SIFT, PolyPhen, Mutation Taster, Mutation assessor, FATHMM, GERP, PhyloP, and SiPhy) and re‐evaluation of frequency in the gnomAD database were performed. Fourteen ACMG‐AMP rules were deemed applicable for SCN5A variant analysis. Results: Four hundred and eighty unique SCN5A variants were identified, the majority of which 425 (88%) were coding variants. One hundred and fifty‐six of 425 (37%) variants were classified as pathogenic/likely pathogenic. Two hundred and fifty‐eight (60%) were classified as variants of uncertain significance, while a further 11 (3%) were classified as benign/likely benign. When considering the subset of variants that were considered "null" variants separately, 95% fulfilled criteria for pathogenicity/likely pathogenicity. In contrast, only 17% of missense variants fulfilled criteria for pathogenicity/likely pathogenicity. Importantly, however, only 25% of missense variants had available functional data, which was a major score driver for pathogenic classification. Conclusion: Based on contemporary ACMG‐AMP guidelines, only a minority of SCN5A variants implicated in BrS fulfill the criteria for pathogenicity or likely pathogenicity.